Biosorpsi Logam Zn Pada Limbah Sintetik Menggunakan Biomassa Campuran Pseudomonas aeruginosa dan Pseudomonas sp - Hidayati Hidayati; Uray Lusiana; Yoyon Suyono (Institution for Industrial Research and Standardization of Industry - Padang, 2013)
Zinc is one of the heavy metals that could be harmful for environment. This metal usually arises from industrial activities. Biosorption of zinc in synthetic waste was conducted using biomass mixture of Pseudomonas aeruginosa and Pseudomonas sp. This research aims to determine the zinc adsorption capacity of the biomass in synthetic waste water. Zinc biosorption was performed at pH 4, room temperature and stirring 800 rpm. Variation of contact time used was 30, 60 and 120 min; and the amount of biomass used was 0.01 g, 0.02 g, 0.03 g, 0.04 g and 0.05 g. The highest zinc biosorption capacity was obtained 25.43% at the time of 120 minutes and the amount of biomass used 0.01 g. The optimum condition for biomass biosorption and removal capacity based on the correlation between experimental data and mathematical models was obtained with the addition of 0.04 g of biomass with correlation coefficient (R ) 1 and 0,965 respectively.ABSTRAK Salah satu logam berat yang berbahaya dari hasil kegiatan industri adalah logam Zn (seng). Biosorpsi logam Zn pada limbah sintetik dilakukan dengan menggunakan biomassa campuran Pseudomonas aeruginosa dan Pseudomonas sp. Penelitian ini bertujuan untuk mengetahui kapasitas biomassa dalam mengadsorpsi logam Zn pada limbah sintetik. Biosorpsi logam Zn dilakukan pada kondisi pH 4, temperatur ruang dan pengadukan 800 rpm. Variasi waktu kontak dilakukan pada 30, 60 dan 120 menit dan menggunakan jumlah biomassa 0,01 g, 0,02 g, 0,03 g, 0,04 g dan 0,05 g. Kapasitas biosorpsi logam Zn tertinggi diperoleh sebesar 25,43% pada waktu 120 menit dengan jumlah biomassa 0,01 g. Kondisi optimum biosorpsi logam Zn berdasarkan korelasi antara data eksperimen dan model matematika diperoleh pada penambahan jumlah biomassa sebesar 0,04 g baik untuk kapasitas biosorpsi logam Zn maupun efisiensi removal logam Zn dengan nilai koefisien korelasi (R2) masing-masing adalah 1 dan 0,965.